CMSS1: A RNA binding protein with pivotal roles in non-small cell lung cancer progression and prognosis - Zhe Fan; Wanyu Liu; Zhiwei Gao; Youfa Liu; Hongyang Hai; Zhenyang Lv (BMC Cancer)
Abstract Background The Cms1 ribosomal small subunit homolog (CMSS1), an RNA-binding protein (RBP), plays a crucial role in tumor development. However, the prognostic and immunological role of CMSS1 in non-small cell lung cancer (NSCLC) remains unclear. Methods Differentially expressed RBP genes were identified using The Cancer Genome Atlas (TCGA) database, and the hub RBP-related gene, CMSS1, was selected through univariate Cox regression analysis and Kaplan-Meier tests. To evaluate the prognostic capacity of the CMSS1, time-dependent receiver operating characteristic curves, Kaplan-Meier curves and multivariate Cox regression analyses were conducted. The relationship between the CMSS1 gene and tumor-infiltrating immune cells was assessed using the ImmuCellAI algorithm. Additionally, a loss-of-function assay was performed to investigate the functional role of CMSS1 in NSCLC cells. Results Bioinformatic analysis revealed that CMSS1, an RBP-related gene, was notably upregulated in NSCLC tumors, with elevated RNA levels correlating with poor prognosis in NSCLC patients. Immune cell infiltration analysis showed that CMSS1 expression was negatively correlated with CD4 T cells and was positively correlated with macrophages and Tregs. Furthermore, RT-qPCR and western blot confirmed the increased CMSS1 mRNA and CMSS1 protein levels in NSCLC cell lines. Significantly, downregulation of CMSS1 inhibited NSCLC cell viability, migration and invasion. Conclusion Our findings suggest that CMSS1 may serve as both a prognostic indicator and a therapeutic target for patients with NSCLC. This study may provide potential guidance for precision therapy and accurate prognosis prediction for patients with NSCLC.